1997
DOI: 10.1161/01.str.28.10.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Suggestive of Apoptosis After Spinal Cord Ischemia in Rabbits

Abstract: Spinal cord ischemia in rabbits induces morphological and biochemical changes suggestive of apoptosis. These data raise the possibility that apoptosis contributes to neuronal cell death after spinal cord ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
3
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 34 publications
1
33
3
1
Order By: Relevance
“…The TUNEL labeling present in ventral horn motor neurons in the saline-treated group, which was almost entirely absent in the rHu-EPO-treated groups, is strongly supportive of an effect of EPO in blocking the induction of an apoptotic program in this class of neurons. Recent studies using this rabbit model have shown that within the first few days following transient spinal cord global ischemia the motor neurons undergo apoptosis (27,28). The results observed here, therefore, confirm these observations as well as demonstrate that rHu-EPO can prevent ischemia-induced programmed cell death.…”
Section: Discussionsupporting
confidence: 89%
“…The TUNEL labeling present in ventral horn motor neurons in the saline-treated group, which was almost entirely absent in the rHu-EPO-treated groups, is strongly supportive of an effect of EPO in blocking the induction of an apoptotic program in this class of neurons. Recent studies using this rabbit model have shown that within the first few days following transient spinal cord global ischemia the motor neurons undergo apoptosis (27,28). The results observed here, therefore, confirm these observations as well as demonstrate that rHu-EPO can prevent ischemia-induced programmed cell death.…”
Section: Discussionsupporting
confidence: 89%
“…This information can be applied not only to domestic animals but also to humans (Cizkova et al, 2001). Furthermore, as an excellent model species, rabbits help to investigate such conditions like arterial injury (Jorgensen et al, 1972), aortic occlusion (Mackey et al, 1997) and aortic aneurysm (Freestone et al, 1997). However, there is limited information about basic anatomy of the rabbit kidney.…”
Section: Introductionmentioning
confidence: 99%
“…All of these risk factors may alter spinal cord blood supply, and finally causing apoptosis and necrosis of neurons [13,14]. Cord dysfunction occurs and even worsens though postoperative immediate neurologic function improves.…”
Section: Disscussionmentioning
confidence: 99%